Glossenkeil and Indentation on Hittite Tablets - Pisaniello, Valerio (Altorientalische Forschungen, 2020)
In this paper, I will address the issue of the use of the Glossenkeil as a mark of indented line in Hittite texts, based on a complete collection of the occurrences of this practice found in the texts published so far. After outlining the main functions of the Glossenkeil in Hittite texts and establishing a typology of line indentations, I will argue that the Glossenkeil should not be properly regarded as a mark of indentation, but as a mark of the beginning of the line, which pointed out that indentation was merely accidental, and should not have been reproduced in future copies of the text. Furthermore, the case of some Hittite words unexpectedly marked by the Glossenkeil will be reconsidered based on the non-lexical functions of this sign. Finally, I will show how the analysis of this scribal practice can be useful for the identification of the hands of the scribes, and, based on it, I will suggest that two manuscripts of the funerary ritual, KUB 30.24+ and KUB 39.7+, were drafted by the same scribe.